An EZH2 blocker sensitizes histone mutated diffuse midline glioma to cholesterol metabolism inhibitors through an off-target effect. Issue 1 (1st March 2022) - Rahal, Farah; Capdevielle, Caroline; Rousseau, Benoit; Izotte, Julien; Dupuy, Jean-William; Cappellen, David; Chotard, Guillaume; Ménard, Mélissa; Charpentier, Justine; Jecko, Vincent; Caumont, Charline; Gimbert, Edouard; et al.
Abstract: Background: Diffuse Midline Glioma, H3K27M-mutant (DMG) is a rare, highly aggressive pediatric tumor affecting the brainstem, and is one of the deadliest cancers. Currently available treatment options such as chemotherapy and radiotherapy do only modestly prolong survival. In this pathology, H3K27 mutations deregulate Polycomb Repressive Complex 2 (PRC2), including enzymatic activity of EZH2, which is therefore under investigation as a therapeutic target. Methods: We used a chemical EZH2 inhibitor, GSK126, small interfering RNAs, and a CRISPR/Cas9 knockout approaches in a series of DMG tumor cell lines to investigate metabolic treatment responses by proteomic analysis. A combination strategy was elaborated and studied in primary and established DMG cells, spheroid 3D cultures, and in vivo in a chick chorio-allantoic membrane DMG assay and an orthotopic intracranial DMG mouse model. Results: GSK126 shows significant ( P < .05–.001) inhibitory effects in in vitro cell proliferation assays and induces apoptosis. Chemical targeting of EZH2 induced expression of proteins implicated in cholesterol metabolism. Low-dose GSK126 treatment together with statins revealed strong growth inhibition in combinatorial treatments, but not in single treatments, both in DMG cells in vitro, in DMG spheroid cultures, and in chick and mouse in vivo models ( P < .05). All statistical tests were two-sided. Conclusions: Our results reveal an unexpected GSK126-inducible sensitivity to cholesterol biosynthesis inhibitors in highly aggressive pediatric glioma that warrants further evaluation as treatment strategy. This combinatorial therapy should have few side effects because of the low doses used to achieve significant anti-tumor activity.